DETERMINAN KEJADIAN HIPERTENSI - Sitorus, Jenti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Hypertension is often referred to as the Silent Killer, because this disease can cause sudden death without a clear warning. Based on Toba Regency, Parsoburan Health Center has the highest incidence of hypertension. The purpose of the study was to determine the determinants of the incidence of hypertension. The research design used in this study was Cross Sectional. The research was conducted in the Parsoburan Health Center work area in August 2023. The study population was all adult women aged 30-49 years who came to the health center. The sample amounted to 51 people. The sampling technique used Accidental Sampling. Data analysis was done univariate and bivariate. The results showed that there was a relationship between physical activity (p value: 0.010) and diet (p value: 0.000) on the incidence of hypertension in productive age. It is recommended that the Puskesmas improve the quality of health services in the community, especially by increasing health counseling.Keywords: Physical Activity, Hypertension, Diet.